Lightweight building material based on waste photovoltaic glass and preparation method and application thereof
By mixing and processing waste photovoltaic glass with foaming agent in a specific proportion, lightweight building materials are prepared, which solves the problem of resource utilization of waste photovoltaic glass, achieves efficient reuse, and provides building materials with lightweight High-strength, thermal and sound insulation performance.
Patent Information
- Application Number
- CN202211273340.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-10-18
AI Technical Summary
The prior art has failed to effectively solve the problem of large-scale reuse of photovoltaic glass in waste silicon solar cell modules, and its complex composition leads to low resource utilization efficiency.
Use waste photovoltaic glass and foaming agents (such as calcium carbonate and sodium carbonate) to mix in specific proportions, and then ball milling, drying, granulating and sintering to prepare lightweight building materials for high-pressure steaming and light aerated concrete Applied in boards.
The reuse efficiency of waste photovoltaic glass has been greatly improved. The lightweight building materials prepared have the advantages of lightweight, high strength, thermal insulation, sound insulation, etc., and are suitable for ALC board fillers without complex physical and chemical treatment.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lightweight building materials and solid waste utilization, and in particular to a lightweight building material based on waste photovoltaic glass and a preparation method and application thereof. Background Art
[0002] There are two main types of photovoltaic glass. One is suitable for silicon solar cells. As cover glass, its main function is to protect the cell from damage by the external environment. The other is transparent conductive glass suitable for thin-film solar cells. Its main function is to serve as an electrode and cover. Transparent conductive glass is generally thinner and difficult to separate from thin-film cells.
[0003] For silicon solar cell modules, the packaging process is generally to sequentially set EVA and a base plate at the bottom of the solar cell, and sequentially set EVA and photovoltaic glass at the top of the solar cell, and hot press to combine the base plate, EVA, solar cell, EVA, and photovoltaic glass, and then put them into the aluminum alloy frame. Therefore, from the perspective of chemical composition, a silicon solar cell module may include: elemental silicon (solar panel), aluminum alloy (more than 95% Al), EVA, photovoltaic glass, and a base plate, wherein the base plate is generally a fluorine-containing resin. That is, from the perspective of chemical composition, waste photovoltaic glass is also very likely to contain one or more of the above-mentioned components. It can be seen that waste photovoltaic glass is a waste with complex components. In addition, the service life of a general silicon solar cell module is about 15-25 years. This means that a large amount of waste will be generated, and it is urgent to explore ways to reuse waste silicon solar cell modules. However, there is no relevant research on the large-scale application of photovoltaic glass waste in the prior art.
[0004] On the other hand, for similar waste glass with complex components, it is generally necessary to undergo a series of physical and chemical separation methods before reuse. For example, in Chinese patent CN111659706A, a method for recycling scrapped automobile glass, the waste automobile glass is sorted, screened, de-impurified, de-filmed, cleaned, dried, and color screened, thereby realizing the recycling of the waste automobile glass. Another example is in Chinese patent CN103191903A, a method for recycling waste LCD panels, an organic solvent is used to remove the upper and lower polarizers of the LCD panel, crush them, and then dissolve them to pre-treat them into a liquid crystal solution and glass fragments, and then soak them in hydrofluoric acid to obtain clean glass fragments and an indium solution (solid after drying) to realize the recycling of waste LCD panels. These methods are more troublesome to handle, and it is difficult to achieve comprehensive utilization of resources, and the reuse efficiency is low. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a lightweight building material based on waste photovoltaic glass and a preparation method thereof, which can consume waste photovoltaic glass in large quantities and realize the resource utilization of waste photovoltaic glass.
[0006] The technical problem that the present invention is to solve is to provide the application of the above-mentioned lightweight building material based on waste photovoltaic glass in high-pressure steam-cured lightweight aerated concrete panels.
[0007] In order to solve the above technical problems, the present invention provides a lightweight building material based on waste photovoltaic glass, which is mainly made of the following raw materials in parts by weight:
[0008] 90-98 parts of waste photovoltaic glass, 2-10 parts of foaming agent;
[0009] Wherein, the waste photovoltaic glass is waste photovoltaic glass generated by monocrystalline silicon solar cell modules and / or polycrystalline silicon solar cell modules.
[0010] As an improvement of the above technical solution, the waste photovoltaic glass is obtained by crushing a monocrystalline silicon solar cell module and / or a polycrystalline silicon solar cell module after removing the connecting wires and frames, and the particle size of the waste photovoltaic glass is ≤80 mesh;
[0011] The SiO in the waste photovoltaic glass 2 Content <77wt%Al 2 O 3 Content ≤5wt%.
[0012] As an improvement of the above technical solution, the waste photovoltaic glass includes, by weight percentage:
[0013] SiO 2 65-75%, Al 2 O 3 0.5-3%, CaO 8-12%, MgO 1-5%, K 2 O 0.01-0.5%, Na 2 O 10-15%, Fe 2 O 3 0.01-0.1%, LOI 2-5%;
[0014] Among them, LOI is the loss on ignition rate of waste photovoltaic glass at 900°C in air atmosphere.
[0015] As an improvement of the above technical solution, the ignition loss rate of the waste photovoltaic glass satisfies the following relationship:
[0016] LOI 400 / LOI 600 ≤1;
[0017] Among them, LOI 600 LOI is the loss on ignition rate of waste glass at 600℃ in air atmosphere. 400 It is the ignition loss rate of waste photovoltaic glass at 400℃ in air atmosphere.
[0018] As an improvement of the above technical solution, the foaming agent is selected from one or more of calcium carbonate, sodium carbonate, and sodium bicarbonate;
[0019] The particle size of the waste photovoltaic glass is ≤80 mesh.
[0020] Correspondingly, the present invention also discloses a method for preparing a lightweight building material based on waste photovoltaic glass, which is used to prepare the above-mentioned lightweight building material based on waste photovoltaic glass, and comprises:
[0021] Mixing 90-98 parts of waste photovoltaic glass and 2-10 parts of foaming agent, forming and firing to obtain a lightweight building material;
[0022] Wherein, the waste photovoltaic glass is waste photovoltaic glass generated by monocrystalline silicon solar cell modules and / or polycrystalline silicon solar cell modules.
[0023] As an improvement of the above technical solution, waste photovoltaic glass, foaming agent and water are added into a ball mill, ball-milled to a particle size of less than 100 mesh, and then dried, granulated and formed; or
[0024] Add waste photovoltaic glass and water into a ball mill, grind to a particle size of less than 100 mesh, and then dry to obtain a first powder; add a foaming agent and water into a ball mill, grind to a particle size of less than 100 mesh, and then dry to obtain a second powder; mix the first powder and the second powder, add water to granulate, and then form; or
[0025] The waste photovoltaic glass and foaming agent are ground into powder by a vertical mill to a particle size of less than 200 meshes, and then water is added to form granules for molding.
[0026] As an improvement of the above technical solution, the temperature curve used for sintering is:
[0027] Room temperature to 300℃, heating time is 5-30min;
[0028] 300℃ to 600℃, heating time is 10-50min;
[0029] 600℃ to firing temperature, heating time is 20-40min;
[0030] Keep at the firing temperature for 5-20 minutes;
[0031] Among them, the sintering temperature is 700-850℃.
[0032] As an improvement of the above technical solution, the temperature curve used for sintering is:
[0033] Room temperature to 300℃, heating time is 15-25min;
[0034] 300℃ to 400℃, heating time is 5-10min;
[0035] 400 to 600℃, heating time is 20-30min;
[0036] 600℃ to firing temperature, heating time is 20-40min;
[0037] Keep at the firing temperature for 5-15 minutes;
[0038] Among them, the sintering temperature is 720-800℃.
[0039] Correspondingly, the present invention also discloses the application of the above-mentioned lightweight building material based on waste photovoltaic glass in high-pressure steam-cured lightweight aerated concrete panels.
[0040] Implementing the present invention has the following advantages:
[0041] 1. The lightweight building material based on waste photovoltaic glass of the present invention is mainly made of waste photovoltaic glass and foaming agent, and the amount of waste photovoltaic glass reaches 90-98 parts, and the foaming agent is only 2-10 parts, which greatly improves the reuse efficiency of waste photovoltaic glass. And the lightweight building material obtained by the present invention has the advantages of light weight, high strength, heat insulation and sound insulation, and can be used as a filler for ALC board.
[0042] 2. The lightweight building material based on waste photovoltaic glass of the present invention is obtained by breaking the silicon solar cell module after removing the connecting wires and frames, and no other complicated physical and chemical treatment is required. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with specific implementation methods.
[0044] The present invention provides a lightweight building material based on waste photovoltaic glass, which is mainly made of the following raw materials in parts by weight: 90-98 parts of waste photovoltaic glass, 2-10 parts of foaming agent;
[0045] Among them, waste photovoltaic glass refers to waste photovoltaic glass produced by monocrystalline silicon solar cell modules and / or polycrystalline silicon solar cell modules. The photovoltaic glass in monocrystalline silicon solar cell modules and polycrystalline silicon solar cell modules is mainly SiO 2 -CaO-Na 2O-series glass can be used in large quantities in silicon-series building materials to improve utilization efficiency.
[0046] Preferably, the waste photovoltaic glass is a waste with a particle size of ≤80 mesh obtained by crushing and screening monocrystalline silicon solar cell modules and / or polycrystalline silicon solar cell modules after removing the connecting wires and frames. After simple sorting, the connecting wires (metal wires, wire coatings) and aluminum frames can be removed to prevent the metal wires from melting prematurely during the later firing process, affecting the uniformity and size of the pores of the lightweight building materials, thereby increasing their bulk density and reducing their compressive strength. Similarly, the wire coating has a high decomposition temperature. If it is not separated, excess gas is easily generated during the foaming stage, affecting the bulk density and compressive strength of the lightweight building materials. Furthermore, by crushing and screening, a portion of organic materials such as EVA and base plates can also be removed to a certain extent to optimize the foaming performance, improve strength, and reduce bulk density. Specifically, when the particle size of the waste photovoltaic glass is greater than 80 mesh, the uniformity of the compressive strength of the lightweight building materials is poor.
[0047] Specifically, in one embodiment of the present invention, the SiO 2 Content <77wt%Al 2 O 3 Content ≤5wt%. Control SiO in waste photovoltaic glass 2 The content is less than 77wt%, which can reduce the content of crystalline silicon and avoid temperature disturbance caused by high temperature oxidation (≥700℃), which will affect the foaming effect, reduce the compressive strength and increase the bulk density. 2 O 3 The content is ≤5wt%, which can reduce the content of elemental aluminum and prevent the elemental aluminum from melting at around 660°C to produce a melt, affecting the foaming effect, thereby reducing the compressive strength and increasing the bulk density.
[0048] Preferably, in one embodiment of the present invention, the waste photovoltaic glass comprises, by weight percentage:
[0049] SiO 2 65-75%, Al 2 O 3 0.5-3%, CaO 8-12%, MgO 1-5%, K 2 O 0.01-0.5%, Na 2 O10-15%, Fe 2 O 3 0.01-0.1%, LOI 2-5%. LOI is the ignition loss rate of waste photovoltaic glass at 900°C in air atmosphere. The bulk density of the lightweight building material prepared from the waste photovoltaic glass based on the above composition is ≤0.55g / cm 3 , compressive strength ≥1MPa.
[0050] Further preferably, in another embodiment of the present invention, the ignition loss rate of the discarded photovoltaic glass is controlled to satisfy the following relationship: LOI 400 / LOI 600 ≤1; more specifically, control LOI 400 / LOI 600 is 0.5-0.8. Among them, LOI 600 LOI is the loss on ignition rate of waste glass at 600℃ in air atmosphere. 400 is the ignition loss rate of waste photovoltaic glass at 400℃ in air atmosphere. Based on this control, the bulk density of lightweight building materials can be obtained to be ≤0.45g / cm 3 , compressive strength ≥1.2MPa.
[0051] Specifically, the amount of waste photovoltaic glass used is 90-98 parts, exemplified by 91 parts, 93 parts, 95 parts, 96 parts or 97 parts, but not limited thereto.
[0052] Specifically, the foaming agent can be selected from one or more of calcium carbonate, sodium carbonate, sodium bicarbonate, but not limited thereto. Preferably, the foaming agent is selected from calcium carbonate or a mineral containing calcium carbonate. Specifically, calcite, limestone, stalactite, marble or dolomite can be selected, but not limited thereto. Further preferably, the foaming agent is selected from calcite.
[0053] Specifically, the amount of the foaming agent is 2-10 parts, exemplified by 2 parts, 3.5 parts, 5 parts, 6.5 parts, 8 parts or 9.5 parts, but not limited thereto.
[0054] Specifically, in one embodiment of the present invention, the raw materials for preparing the lightweight building material may also include 0-1 part of high-aluminum filler. Specifically, the high-aluminum filler may be high-aluminum minerals such as alumina, mullite, bauxite, etc., but is not limited thereto. The compressive strength of the lightweight building material with high-aluminum filler.
[0055] Correspondingly, the present invention also discloses a method for preparing the above-mentioned lightweight building material, comprising:
[0056] Mixing 90-98 parts of waste photovoltaic glass and 2-10 parts of foaming agent, forming and firing to obtain a lightweight building material;
[0057] Specifically, a wet ball milling process can be used for mixing and powdering, or a dry powdering process can be used for powdering. Specifically, in one embodiment of the present invention, waste photovoltaic glass, foaming agent, and water are added to a ball mill, ball-milled to a particle size of less than 100 meshes to obtain a slurry, and then the slurry (containing 33-37wt% water) is dried and granulated to obtain a powder (water content 5-8wt%). Specifically, dry granulation can be carried out using a spray drying tower, or the slurry can be completely dried and then granulated with water. In another embodiment of the present invention, waste photovoltaic glass and foaming agent can be separately ball-milled with water to a particle size of less than 100 meshes, and then each can be dried and granulated with water to obtain a powder (water content 5-8wt%). In another embodiment of the present invention, waste photovoltaic glass and foaming agent are ground to less than 200 meshes using a vertical mill, and then water is added to granulate to obtain a powder (water content 5-8wt%). In another embodiment of the present invention, the waste photovoltaic glass and the foaming agent can be ground to less than 200 meshes by a vertical mill, and then water is added to granulate to obtain a powder (water content 5-8wt%).
[0058] Specifically, the molding can be dry pressing molding by equipment or powder heap molding in a sagger. Preferably, the dry pressing molding is performed by a conventional ceramic press. Preferably, the green body obtained by molding is dried after molding.
[0059] Specifically, the firing can be carried out in a roller kiln, a tunnel kiln, or a shuttle kiln, but is not limited thereto. The temperature curve used for the firing is:
[0060] Room temperature to 300℃, heating time is 5-30min; in this stage, the small amount of residual free water in the blank is dried. 300℃ to 600℃, heating time is 10-50min; in this stage, the EVA and fluorine-containing resin base introduced by the waste photovoltaic glass are decomposed. If the temperature rises too fast, the decomposition is incomplete, which affects the later foaming. 600℃ to the firing temperature, heating time is 20-40min; keep warm at the firing temperature for 5-20min; the firing temperature is 700-850℃.
[0061] Preferably, in one embodiment of the present invention, the heating time from 300°C to 400°C is 5-10 minutes. At this stage, the fluorine-containing resin is mainly decomposed, and its decomposition is fast, and it can be completely decomposed in a short time. From 400°C to 600°C, at this stage, EVA and the matrix (such as PET) in the bottom plate are mainly decomposed, and the decomposition amount is high, so a longer heating time is used.
[0062] Specifically, after the firing is completed, the product is naturally cooled to room temperature. Preferably, in one embodiment of the present invention, the product obtained by firing is crushed to obtain a particle size of 1-4 mm, that is, a finished lightweight building material is obtained. The lightweight building material has the advantages of light weight, high strength, heat insulation and sound insulation, and can be used as a filler for ALC boards.
[0063] The present invention will be further described below with specific embodiments:
[0064] Example 1
[0065] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0066] 90 parts of waste photovoltaic glass and 10 parts of foaming agent;
[0067] Among them, waste photovoltaic glass is the waste with a maximum particle size of 60 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is calcite.
[0068] The chemical composition of waste photovoltaic glass is as follows:
[0069] SiO 2 68.3%, Al 2 O 3 4.5%, CaO 8.8%, MgO 1.5%, K 2 O 0.03%, Na 2 O 11.45%, Fe 2 O 3 0.02%, LOI 900 5.4%. Among them, LOI 600 LOI is 3.21% 400 It is 2.18%.
[0070] The preparation method of the lightweight building material in this embodiment is as follows:
[0071] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.5wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0072] Room temperature to 300°C, heating time is 30min;
[0073] 300℃ to 400℃, heating time is 15min;
[0074] 400 to 600°C, heating time 35min;
[0075] 600℃ to firing temperature, heating time is 20min;
[0076] Keep at the firing temperature for 20 minutes; wherein the firing temperature is 700°C.
[0077] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0078] Example 2
[0079] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0080] 98 parts of waste photovoltaic glass and 2 parts of foaming agent;
[0081] Among them, the waste photovoltaic glass is the waste with a maximum particle size of 60 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is dolomite.
[0082] The chemical composition of waste photovoltaic glass is as follows:
[0083] SiO 2 68.3%, Al 2 O 3 4.5%, CaO 8.8%, MgO 1.5%, K 2 O 0.03%, Na 2 O 11.45%, Fe 2 O 3 0.02%, LOI 900 5.4%. Among them, LOI 600 LOI is 3.21% 400 It is 2.18%.
[0084] The preparation method of the lightweight building material in this embodiment is as follows:
[0085] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.3wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0086] Room temperature to 300°C, heating time is 5min;
[0087] 300℃ to 400℃, heating time is 10min;
[0088] 400 to 600°C, heating time is 15min;
[0089] 600℃ to firing temperature, heating time is 40min;
[0090] Keep at the firing temperature for 5 minutes; wherein the firing temperature is 850°C.
[0091] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0092] Example 3
[0093] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0094] 97 parts of waste photovoltaic glass and 3 parts of foaming agent;
[0095] Among them, the waste photovoltaic glass is the waste with a maximum particle size of 80 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is calcite.
[0096] The chemical composition of waste photovoltaic glass is as follows:
[0097] SiO 2 71.4%, Al 2 O 3 2.7%, CaO 9.3%, MgO 1.1%, K 2 O 0.2%, Na 2 O 10.57%, Fe 2 O 3 0.08%, LOI 900 4.65%. Among them, LOI 600 LOI is 2.35% 400 It is 2.3%.
[0098] The preparation method of the lightweight building material in this embodiment is as follows:
[0099] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.5wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0100] Room temperature to 300°C, heating time is 20min;
[0101] 300℃ to 400℃, heating time is 10min;
[0102] 400 to 600°C, heating time is 20min;
[0103] 600℃ to firing temperature, heating time is 30min;
[0104] Keep at the firing temperature for 10 minutes; wherein the firing temperature is 800°C.
[0105] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0106] Example 4
[0107] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0108] 97 parts of waste photovoltaic glass and 3 parts of foaming agent;
[0109] Among them, the waste photovoltaic glass is the waste with a maximum particle size of 90 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is calcite.
[0110] The chemical composition of waste photovoltaic glass is as follows:
[0111] SiO 2 70.24%, Al 2 O 3 1.61%, CaO 10.71%, MgO 2.8%, K 2 O 0.04%, Na 2 O12.34%,Fe 2 O 3 0.05%, LOI 900 2.21%. Among them, LOI 400 LOI is 1.05% 600 It is 1.16%.
[0112] The preparation method of the lightweight building material in this embodiment is as follows:
[0113] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.5wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0114] Room temperature to 300°C, heating time is 20min;
[0115] 300℃ to 400℃, heating time is 10min;
[0116] 400 to 600°C, heating time is 20min;
[0117] 600℃ to firing temperature, heating time is 30min;
[0118] Keep at the firing temperature for 10 minutes; wherein the firing temperature is 800°C.
[0119] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0120] Example 5
[0121] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0122] 97 parts of waste photovoltaic glass and 3 parts of foaming agent;
[0123] Among them, the waste photovoltaic glass is the waste with a maximum particle size of 90 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is calcite.
[0124] The chemical composition of waste photovoltaic glass is as follows:
[0125] SiO 2 70.24%, Al 2 O 3 1.61%, CaO 10.71%, MgO 2.8%, K 2 O 0.04%, Na 2 O12.34%,Fe 2 O 3 0.05%, LOI 900 2.21%. Among them, LOI 400 LOI is 1.05% 600 It is 1.16%.
[0126] The preparation method of the lightweight building material in this embodiment is as follows:
[0127] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.5wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0128] Room temperature to 300°C, heating time is 20min;
[0129] 300℃ to 400℃, heating time is 8min;
[0130] 400 to 600°C, heating time is 22 minutes;
[0131] 600℃ to firing temperature, heating time is 30min;
[0132] Keep at the firing temperature for 10 minutes; wherein the firing temperature is 800°C.
[0133] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0134] Example 6
[0135] This embodiment provides a lightweight building material based on waste photovoltaic glass, and its raw material formula is:
[0136] 97 parts of waste photovoltaic glass and 3 parts of foaming agent;
[0137] Among them, waste photovoltaic glass is the waste with a maximum particle size of 100 mesh obtained by crushing and screening the monocrystalline silicon solar cell modules after removing the connecting wires and frames, and the foaming agent is calcite.
[0138] The chemical composition of waste photovoltaic glass is as follows:
[0139] SiO 2 70.7%,Al 2 O 3 1.51%, CaO 9.78%, MgO 2.24%, K 2 O 0.03%, Na 2 O 13.5%, Fe 2 O 3 0.05%, LOI 900 2.19%. Among them, LOI 600 LOI is 0.89% 400 It is 1.3%.
[0140] The preparation method of the lightweight building material in this embodiment is as follows:
[0141] According to the formula, 100g of ingredients were added with 50g of water, ball-milled to a fineness of 0.5wt% with a 200-mesh sieve residue, spray-dried to obtain a powder, and pressed into two pieces with a size of 5×10cm 2 The green body is dried in an oven at 100℃ for 1 hour and then fired in an electric furnace. The specific firing curve is:
[0142] Room temperature to 300°C, heating time is 20min;
[0143] 300℃ to 400℃, heating time is 8min;
[0144] 400 to 600°C, heating time is 22 minutes;
[0145] 600℃ to firing temperature, heating time is 30min;
[0146] Keep at the firing temperature for 10 minutes; wherein the firing temperature is 800°C.
[0147] Then cool to room temperature in the furnace and finally crush to particle size of 1-3mm.
[0148] The samples that were not broken after firing in Examples 1-6 were tested for compressive strength and bulk density, respectively. The specific results are as follows:
[0149] <![CDATA[Bulk density (g / cm 3 )]]> Compressive strength(MPa) Example 1 0.55 0.85 Example 2 0.47 0.88 Example 3 0.35 1.08 Example 4 0.31 1.22 Example 5 0.28 1.25 Example 6 0.22 1.38
[0150] It can be seen from the table that the lightweight building material prepared by the present invention has a compressive strength of ≥0.85MPa and a bulk density of ≤0.55g / cm 3 .
[0151] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.
Claims
1. A method for preparing a lightweight building material based on waste photovoltaic glass, characterized in that: include: Mixing 90-98 parts of waste photovoltaic glass and 2-10 parts of foaming agent, forming and firing to obtain a lightweight building material; Wherein, the waste photovoltaic glass is the waste with a mesh size of ≤80 obtained by crushing and screening the monocrystalline silicon solar cell modules and / or polycrystalline silicon solar cell modules after removing the connecting wires and frames; The SiO2 content in the waste photovoltaic glass is less than 77wt%, and the Al2O3 content is less than 5wt%; Among them, the temperature curve used for firing is: Room temperature to 300℃, heating time is 5-30min; 300℃ to 600℃, heating time is 10-50min; 600℃ to firing temperature, heating time is 20-40min; Keep at the firing temperature for 5-20 minutes; Among them, the sintering temperature is 700-850℃.
2. The method for preparing a lightweight building material based on waste photovoltaic glass according to claim 1, characterized in that: The waste photovoltaic glass includes, by weight percentage: SiO2 65-75%, Al2O3 0.5-3%, CaO 8-12%, MgO 1-5%, K2O 0.01-0.5%, Na2O10-15%, Fe2O3 0.01-0.1%, LOI 2-5%; Among them, LOI is the loss on ignition rate of waste photovoltaic glass at 900°C in air atmosphere.
3. The method for preparing a lightweight building material based on waste photovoltaic glass according to claim 1, characterized in that: The ignition loss rate of the waste photovoltaic glass satisfies the following relationship: LAW 400 / LAW 600 ≤1; Among them, LOI 600 LOI is the loss on ignition rate of waste glass at 600℃ in air atmosphere. 400 It is the ignition loss rate of waste photovoltaic glass at 400℃ in air atmosphere.
4. The method for preparing a lightweight building material based on waste photovoltaic glass according to claim 1, characterized in that: The foaming agent is selected from one or more of calcium carbonate, sodium carbonate and sodium bicarbonate.
5. The method for preparing a lightweight building material based on waste photovoltaic glass according to claim 1, characterized in that: Add waste photovoltaic glass, foaming agent and water into a ball mill, grind to a particle size of less than 100 mesh, and then dry, granulate and shape; or Add waste photovoltaic glass and water into a ball mill, grind to a particle size of less than 100 mesh, and then dry to obtain a first powder; add a foaming agent and water into a ball mill, grind to a particle size of less than 100 mesh, and then dry to obtain a second powder; mix the first powder and the second powder, add water to granulate, and then form; or The waste photovoltaic glass and foaming agent are ground into powder by a vertical mill to a particle size of less than 200 meshes, and then water is added to form granules.
6. The method for preparing a lightweight building material based on waste photovoltaic glass according to claim 1, characterized in that: The temperature curve used for firing is: Room temperature to 300℃, heating time is 15-25min; 300℃ to 400℃, heating time is 5-10min; 400 to 600℃, heating time is 20-30min; 600℃ to firing temperature, heating time is 20-40min; Keep at the firing temperature for 5-15 minutes; Among them, the sintering temperature is 720-800℃.
7. A lightweight building material based on waste photovoltaic glass, characterized in that: The lightweight building material is prepared by the method for preparing a lightweight building material based on waste photovoltaic glass as described in any one of claims 1 to 6.
8. Use of the lightweight building material based on waste photovoltaic glass as claimed in claim 7 in high-pressure steam-cured lightweight aerated concrete panels.
Citation Information
Patent Citations
Method for recycling waste LCD (liquid crystal display) panels
CN103191903A
Scraped car glass recovery treatment method
CN111659706A
Air-added brick taking hollow glass beads as filler and method for processing air-added brick
CN102887675A